Contrariety and Complementarity: Reading Spinoza’s Intersubjective Holism of Ideas with Aristotle’s Two Accounts of Motion - Lorina Buhr (Journal of Spinoza Studies, 2023)
Do minds and ideas connect, interact, or even depend on each other, and if so, how exactly do they connect and interact? How to conceive of the mode and process of minds and ideas being in a network and connected in some way, that is, being intersubjective or social? Martin Lenz’s study Socializing Minds (2022) convincingly shows that, contrary to widespread opinion in philosophy of mind, at least some early modern philosophers, here Spinoza, Locke, and Hume, actually give a positive answer to the first question and present models that respond to the second question, thus, addressing what Lenz proposes to call ‘the contact problem’ and repudiating the idea that mentalism is necessarily bound to individualism. In this comment, I focus on a detail in Lenz’s reconstruction of Spinoza’s ‘metaphysical model’ of intersubjectivity of minds, namely the Aristotelian physical dynamism that would underlie Spinoza’s idea of the interaction of minds. While I agree that Spinoza’s model of the interaction of minds refers to the Aristotelian conception of motion, I argue that the guiding principle in natural motion is best understood not only in terms of contrariety but also in terms of complementarity. A closer reading of Aristotle’s theory of motion (kinēsis, metabolē) identifies two approaches to natural motion, one based on contrary principles, the other on complementary principles or powers (dynameis; potentiae). I suggest conceiving them as two sources for modelling natural motion and thus as two resources for a kinetic modelling of intersubjectivity and sociality. Admittedly, my proposal goes beyond Spinoza’s model of ideas in contact, and probably beyond Lenz's interpretation of that model, but it might enrich the imagination of the socialising of minds and ideas from a kinetic point of view, which, at least as I understand it, is precisely what Spinoza and Lenz thrive on.